MENINGKATKAN KEAKTIFAN SISWA MELALUI MEDIA MARBEL BUDAYA NUSANTARA DALAM PEMBELAJARAN IPAS DI SEKOLAH DASAR - Debby Feriska; Nana Sutarna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to find out information regarding the effect of implementing the Marbel Budaya Nusantara learning media on the active learning of fourth-grade students in the subject of Natural and Social Sciences (IPAS). In this research, the method used was Quasi Experimental with a non-equivalent control group design. The sampling technique used purposive sampling, selecting class IV A as the experimental class and IV B as the control class. Data collection used questionnaires and observation sheets. Based on the research results, it can be concluded that the use of Marbel Budaya Nusantara learning media can increase student learning activeness. This is evident from the average scores, with the experimental class obtaining 54.41 and the control class 44.30, showing a difference of 10.11 points. The results of the Independent Sample t-Test data analysis using SPSS version 27 showed a significance value (2-tailed) = 0.000 < 0.05. Ho was rejected and Ha was accepted, which means that the implementation of the Marbel Budaya Nusantara learning media has a significant effect on the learning activeness of fourth-grade students in the IPAS subject.